Risk Factors for Development of a Recalcitrant Femoral Nonunion: A Single Surgeon Experience in 122 Patients. Issue 12 (December 2021) - Wiss, Donald A.; Garlich, John; Hashmi, Sohaib; Neustein, Adam
Abstract : Supplemental Digital Content is Available in the Text. Abstract : Objectives: The goals of the study were (1) to document the healing rates of femoral nonunions stratified by those that healed as intended, healed after a subsequent intervention, and those that did not heal; (2) to report the prevalence of recalcitrant femoral nonunions and (3) to identify specific demographic, injury, and treatment-related risk factors for the development of a recalcitrant nonunion. Design: Longitudinal observational cohort study. Setting: Academic Level 1 trauma center. Patients/Participants: One hundred twenty-two femoral nonunions treated with either a plate or intramedullary nail by a single surgeon between 1991 and 2018. Intervention: Bivariate and multivariate regression analysis were performed to identify specific demographic, injury, and treatment factors in patients who developed a recalcitrant nonunion. Results: Although 83.6% of the femoral nonunions eventually healed, only 66% "healed as intended" with 17.2% requiring 1 or more additional procedures to consolidate and 16.4% of nonunions failing to unite. There were no statistically significant differences in the recalcitrance rate when we compared treatment with conventional versus locked plates or primary versus exchange nailing. Risk factors for developing a recalcitrant nonunion were deep infection, current smokers, metabolic bone disease, and patients who had undergone 3 or more prior surgical procedures. Conclusions: The use of both intramedullary nails and modern plates were associated with a high rate of recalcitrance. Infection, current smokers, metabolic bone disease, and 3 or more prior surgical procedures were predictors for the development of a recalcitrant nonunion. Level of Evidence: Therapeutic Leve IV. See Instructions for Authors for a complete description of levels of evidence.